Characteristics of Hydrated Cement Treated Crushed Rock Base (HCTCRB) for Western Australian Roads - Chummuneerat, Suphat; Jitsangiam, Peerapong; Nikraz, Hamid (International Committee on Road & Airfield Pavement Technology (ICPT), 2011)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is a unique base course material instigated and broadened in Western Australia roads. The HCTCRB concept was originated by blending small amount (1 to 2% by mass) of Portland cement with standard crushed rock base (CRB) at an optimum amount of water. The mix is stored for some specific hydration periods (7 to 90 days) and then remixed in order to break the cementitous bond before construction. HCTCRB was initiated, and being developed, to accomplish the disadvantages of conventional CRB and cemented treated crushed rock base which tends to exhibit the fatigue deterioration. HCTCRB is expected to provide higher shear strength and lower moisture sensitivity than CRB while avoid significant tensile strength and bound characteristic that lead to fatigue and crack problems as appear in cement treated base. Nevertheless, its application is in doubt regarding the proper qualities and proportion of mixing materials, mixing and curing process, and construction procedures. Thus, effects of such abundant factors governing the HCTCRB properties during manufacturing and construction have to be more investigated. This research exhibits the physical and performance characteristics of HCTCRB -in comparison with that of standard CRB. The experiments were conducted in various conditions (hydration periods, moisture contents, and degree of compaction) to examine the physical properties such as gradation and surface property, and performance characteristics such as shear strength parameters, resilient modulus and permanent deformation. The research outcome leads to further enhancement of HCTCRB using mechanistic approach for analysis, design and modelling.